Pengaruh Kegiatan Camp To Healing Terhadap Self Affirmation Remaja Broken Home Pada Komunitas BEHOME.ID - Nur Rahmawati, Silfi; Kusnadi, Kusnadi; Noviza, Neni (Social Science and Contemporary Issues Journal, 2023)
in the Behome.Id Community". The background of this research is that there are many broken home teenagers who experience an identity crisis and a lack of self-esteem that underlies low self-affirmaThis research is entitled "The Influence of Camp To Healing Activities on Self-Affirmation of Broken Home Youth tion or you can say a low level of self-esteem, in this case a community in Indonesia, namely Behome.Id, participates taking part in being a forum for broken home youth to develop themselves and holding various activities to solve this problem, one of which is the Camp To Healing Activity. This study aims to determine how much influence Camp To Healing activities have on the Self-Affirmation of broken home youth in the Behome.Id community. This study uses quantitative research. The population of this study was 17 people, namely participants in the camp to healing vol. 1 Bandar Lampung, according to Arikunto that if the population is less than 100 then it is better to take the entire population to be sampled, therefore researchers take the entire population to be sampled. The results of this study are, the behome.Id community is a good place for broken home teenagers where one of its activities, namely camp to healing, has quite an effect on the broken home youth's self-affirmation which has been proven in several tests in the methodology quantitatively and it can be concluded that camp to healing activities (variable X) affect the self-affirmation of broken home youth in the Behome.Id community (variable Y).